# 5-(2w-2)=3(3w-8)

## Simple and best practice solution for 5-(2w-2)=3(3w-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5-(2w-2)=3(3w-8) equation:

Simplifying
5 + -1(2w + -2) = 3(3w + -8)

Reorder the terms:
5 + -1(-2 + 2w) = 3(3w + -8)
5 + (-2 * -1 + 2w * -1) = 3(3w + -8)
5 + (2 + -2w) = 3(3w + -8)

Combine like terms: 5 + 2 = 7
7 + -2w = 3(3w + -8)

Reorder the terms:
7 + -2w = 3(-8 + 3w)
7 + -2w = (-8 * 3 + 3w * 3)
7 + -2w = (-24 + 9w)

Solving
7 + -2w = -24 + 9w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-9w' to each side of the equation.
7 + -2w + -9w = -24 + 9w + -9w

Combine like terms: -2w + -9w = -11w
7 + -11w = -24 + 9w + -9w

Combine like terms: 9w + -9w = 0
7 + -11w = -24 + 0
7 + -11w = -24

Add '-7' to each side of the equation.
7 + -7 + -11w = -24 + -7

Combine like terms: 7 + -7 = 0
0 + -11w = -24 + -7
-11w = -24 + -7

Combine like terms: -24 + -7 = -31
-11w = -31

Divide each side by '-11'.
w = 2.818181818

Simplifying
w = 2.818181818`